Lifestyle and treatment adherence among overweight adolescents. (April 2016) - Sousa, Pedro; Gaspar, Pedro; Fonseca, Helena; Gaspar, Filomena
This study evaluated the influence of overweight adolescents' lifestyle on the adherence to weight control, and identifies their predictors. Participants were 94 adolescents, aged 12–18 years, attending a Paediatric Obesity Clinic. Lifestyle was assessed using the "Adolescent Lifestyle Profile" and treatment adherence through the "Therapeutic Adherence to Weight Control Questionnaire." Adherence to weight control was associated with various lifestyle domains. Several predictors were identified for lifestyle and adherence to weight control among overweight adolescents. A broad array of inter-correlations and predictors were identified and should be taken into account when designing adolescent weight control interventions.